Social movement unionism and the Kilusang Mayo Uno - Scipes, Kim (Kasarinlan: Philippine Journal of Third World Studies, 1992)
Trade unionism in the less economically developed countries (LEDCs) in crisis: low rates of industrialization, state opposition and/or cooptation, incompetent and/or self-serving leadership, and poor membership participation dog most trade unions. Meanwhile, countries are manipulated by the multinational corporations into competing for a limited amount of investment, the International Monetary Fund (IMF) and the World Bank (WB) are restructuring economies for the purpose of increasing exploitation and powerlessness, capital is making high rates of profit, workers are exploited, and the living standards for all who must sell their labor to survive and their families continue to decrease.